Cinnamaldehyde and terpineol as inhibitors of Candida albicans and Enterococcus faecalis biofilms - Maria Heloísa de Souza Borges; Nadiny Cezar Rodrigues; Arella Cristina Muniz Brito; Isis Morais Bezerra; Leopoldina de Fátima Dantas de Almeida (Editorial Ciencias Médicas, 2021)
Introduction: Phytoconstituents are natural molecules displaying satisfactory antimicrobial activity. Studies should be conducted about their use as new root canal irrigants. Objective: Evaluate the inhibitory effect of the phytoconstituents cinnamaldehyde and α-terpineol against mono- and duo-species biofilms of microorganisms involved in endodontic infection. Methods: An experimental applied microbiology blind randomized in vitro study was conducted. The phytoconstituents selected were cinnamaldehyde and α-terpineol. Antimicrobial activity against Candida albicans and Enterococcus faecalis was evaluated by metabolic capacity analysis with resazurin and cell viability analysis by the plaque. The culture medium and 1% chlorhexidine served as negative and positive controls, respectively. Results: An absence of growth was observed for exposure of the biofilms at concentrations of 10 and 5 mg/ml of both phytoconstituents. At a concentration of 2.5 mg/ml terpineol displayed growth only in the mono-species biofilms of C. albicans and duo-species biofilms. At a concentration of 1 mg/ml terpineol and cinnamaldehyde displayed growth in all biofilms. Conclusions: Cinnamaldehyde and α-terpineol displayed inhibitory activity against mono- and duo-species biofilms of Candida albicans and Enterococcus faecalis at concentrations of 10 and 5 mg/ml.